(untitled) (MMIT Proceedings, 2025)
The article analyzes cognitive learning theory with a focus on its practical application in educational settings. It discusses key concepts of cognitivism, including the role of memory, thinking, and internal mental activity of learners. Specific pedagogical methods based on cognitive principles are presented: concept maps, problem-based learning, and metacognitive strategies. The study concludes that the cognitive approach is essential for fostering critical thinking, self-regulation, and the development of durable knowledge acquisition skills